Κλωνοποίηση μιας λακκάσης από το μύκητα Μyceliophthora thermophila -Βιοτεχνολογική αξιολόγηση εμπορικής λακκάσης σε αντιδράσεις πολυμερισμού - Κιλιμτζίδη, Ευμορφία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2015)
The present thesis focuses on both cloning and heterologous expression of agene from the thermophilic fungus M.thermophila encoding a novel enzyme(laccase), as well as the use of the commercial laccase for polymerization reactions. At first a procedure for the isolation of the total DNA from M. thermophila was performed. The nucleotide sequence of the gene was recovered from the Genome Portal database and this was followed by the in vitro quantitative amplification of the gene from the genomic DNA sample using polymerase chain reaction. The design of the primers was based on the nucleotide sequence that was going to be cloned with the aid of bioinformatics program. The nucleotide sequence was inserted into the plasmid cloning vector pCR® Blunt via a ligation reaction and transformation of competent bacterial cells E. coli followed. The overlap extension polymerase chain reaction method was used to amplify the three coding regions of the gene and produce DNA fragments consisting of the three regions spliced together. The products were inserted into the pCR® Blunt vector in order to transform cells of the bacterium E. coli. The DNA sequence was isolated and inserted into the plasmid vector pPICZαA and the recombinant plasmids were used to transform E.coli strains. After the isolation and the linearization of the recombinant plasmid, a procedure for transformation of eukaryotic cells of the yeast P.pastoris by electroporation was performed. The expression of the heterologous sequence in the modified strains was studied in small scale cultures. The study showed satisfactory levels of biomass growth, while no enzyme activity was detected when the enzyme was assayed in the presence of ABTS subst rate. Nevertheless, an attempt to recover the protein was made. In order to evaluate the biotechnological value of the commercial laccase, the polymerization of a variety of aromatic compounds was also studied. The optimization of this process was based on the molecule of catechol, which structure is one of the simplest of those of aromatic compounds. The optimum yield of the reactions observed in temperature equal to 30 ° C and pH = 6. Furthermore, the polymerization of other aromatic compounds such as pyrogallol, catechin, gallic acid, aniline, hydroquinone, quercetin and caffeic acid was examined. For most of these compounds, the results that were obtained were similar to thoseof the polymerization of catechol.